Designing Drone Game for Construction Site Inspection - Lawani, Kenneth; Hare, Billy; Cameron, Iain; Homatash, Hamid; Campbell, Julie (Frontiers in Built Environment, 2022)
The use of drone technology in the construction sector promises faster and more streamlined working practices. Forward-thinking contractors are investing in digitizing their operations and the use of drones with the capability of providing real-time site information is already a reality. Deploying drones for site inspections can help construction and safety managers avoid placing workers in precarious situations and the ability to quickly gather site aerial data can be invaluable. This study focuses on creating a drone flying game for inspecting a virtual construction site and identifying potential safety hazards. The single-player, user-focused game is built using the Unity game engine for WebGL which renders interactive 3D graphics to be played in modern web browsers without the use of plug-ins. The game’s aim is to give a simulated experience of piloting a drone and using it to identify potential hazards in an active simulated construction site, and educating players of the effectiveness of using drones for this task, without the real-world risk of collision, damage or injury. Preliminary findings from 47 purposive sampled participants revealed that the drone game was engaging; participants found the game intuitive to use and easy to pilot the drone; the hazards and the simulated construction environment were realistic; and the game satisfies the main aim of highlighting the benefits of using drones on a construction site. The target audience for user experience and usability testing are construction and safety managers, construction professionals and students working in the industry. The skills acquired from playing the educational drone game for virtual construction site inspection and monitoring could be successfully applied when flying a real drone on a live construction site. The significance of learning how to fly drones for site inspection during Covid-19 pandemic where workers need to be physically distanced is timely and relevant.